HUKUM ISLAM DANMUAMALAH (Asas-asas hukum Islam dalam bidang muamalah) - Abdul Munib (Universitas Islam Madura, 2018)
Islam is a religion serves as the rahmatal lil alamin,regulates the relation between khaliq and creatures. Islam comes as a regulator of relationships among human beings, such as buy and sells law, marriage, inheritance, etc., the goal is to get peace of people live, justice and love between eachother. The fundamental pinciple statement can be used as a guide of thought and action, arise principles from the results of research and action, the principle is permanent, general and every science has a principle that reflects the